Influence of Light and Temperature on Gene Expression Leading to Accumulation of Specific Flavonol Glycosides and Hydroxycinnamic Acid Derivatives in Kale (Brassica oleracea var. sabellica) - Neugart, Susanne; Krumbein, Angelika; Zrenner, Rita (Frontiers in Plant Science, 2016)
Light intensity and temperature are very important signals for the regulation of plant growth and development. Plants subjected to less favorable light or temperature conditions often respond with accumulation of secondary metabolites. Some of these metabolites have been identified as bioactive compounds, considered to exert positive effects on human health when consumed regularly. In order to test a typical range of growth parameters for the winter crop Brassica oleracea var. sabellica, plants were grown either at 400 µmol m-2 s-1 or 100 µmol m-2 s-1 at 10°C, or at 400 µmol m-2 s-1 with 5°C or 15°C. The higher light intensity overall increased flavonol content of leaves, favoring the main quercetin glycosides, a caffeic acid monoacylated kaempferol triglycoside, and disinapoyl-gentiobiose. The higher temperature mainly increased the hydroxycinnamic acid derivative disinapoyl-gentiobiose, while at lower temperature synthesis is in favor of very complex sinapic acid acylated flavonol tetraglycosides such as kaempferol-3-O-sinapoyl-sophoroside-7-O-diglucoside. A global analysis of light and temperature dependent alterations of gene expression in B. oleracea var. sabellica leaves was performed with the most comprehensive Brassica microarray. When compared to the light experiment much less genes were differentially expressed in kale leaves grown at 5°C or 15°C. A structured evaluation of differentially expressed genes revealed the expected enrichment in the functional categories of e.g. protein degradation at different light intensities or phytohormone metabolism at different temperature. Genes of the secondary metabolism namely phenylpropanoids are significantly enriched with both treatments. Thus, the genome of B. oleracea was screened for predicted genes putatively involved in the biosynthesis of flavonoids and hydroxycinnamic acid derivatives. All identified B. oleracea genes were analyzed for their most specific 60-mer oligonucleotides present on the 2 × 105K format Brassica microrray. Expression differences were correlated to the structure-dependent response of flavonoid glycosides and hydroxycinnamic acid derivatives to alterations in either light or temperature. The altered metabolite accumulation was mainly reflected on gene expression level of core biosynthetic pathway genes and gave further hints to an isoform specific functional specialization.